2017
DOI: 10.1519/jsc.0000000000002231
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Vertical Jump as a Measure of Neuromuscular Readiness and Fatigue

Abstract: Watkins, CM, Barillas, SR, Wong, MA, Archer, DC, Dobbs, IJ, Lockie, RG, Coburn, JW, Tran, TT, and Brown, LE. Determination of vertical jump as a measure of neuromuscular readiness and fatigue. J Strength Cond Res 31(12): 3305-3310, 2017-Coaches closely monitor training loads and periodize sessions throughout the season to create optimal adaptations at the proper time. However, only monitoring training loads ignores the innate physiological stress each athlete feels individually. Vertical jump (VJ) is widely us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 30 publications
1
59
0
3
Order By: Relevance
“…In our investigation, we found the vertical jump test to have a high agreement between trials, although this measure was better among girls than among boys. Hypothetically, the differences in jump height between trials can be due to systematic bias, such as the athlete's emotional stress (Schaal et al, 2011) or fatigue (Watkins et al, 2017), and variation in jumping mechanics (Attia et al, 2017). However, our overall findings indicate that the horizontal jump test and the vertical jump test may be an appropriate ecologic alternative to laboratory tests examining lower limb strength.…”
Section: Discussionmentioning
confidence: 99%
“…In our investigation, we found the vertical jump test to have a high agreement between trials, although this measure was better among girls than among boys. Hypothetically, the differences in jump height between trials can be due to systematic bias, such as the athlete's emotional stress (Schaal et al, 2011) or fatigue (Watkins et al, 2017), and variation in jumping mechanics (Attia et al, 2017). However, our overall findings indicate that the horizontal jump test and the vertical jump test may be an appropriate ecologic alternative to laboratory tests examining lower limb strength.…”
Section: Discussionmentioning
confidence: 99%
“…For example, following exercise that heavily utilises the stretch shortening cycle (SSC), such as endurance running, reductions in drop jump, but not CMJ height, have been reported 9 . Additionally, fatigue-induced changes in CMJ height are correlated with the back-squat load but not any other mechanically dissimilar exercises 10 . The two wicket keepers in the study showed a relatively large change of 10% CMJ height.…”
Section: Discussionmentioning
confidence: 92%
“…In conjunction with further exploring the alterations in jump strategy associated with changing neuromuscular function, the suitability of one test to assess neuromuscular function within a team has not been fully explored. Previous research demonstrates that there appears to be a task specificity to assessing neuromuscular function 9,10 . Given the multitude of different biomechanical and physiological requirements in cricket 11 it may be the case a single test will not capture the neuromuscular demands of each position and consequently not be a suitable to detect changes in fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…A simulation-based approach was adopted to quantify the effects of measurement error and testing frequency on fitness-fatigue model parameter estimates and performance prediction for two hypothetical athletes (intermediate and advanced). The vertical jump was selected as the performance measurement tool due to its popularity in athlete monitoring and potential to be used daily [20]. A range of mechanical variables including power, impulse and jump height were considered for the simulation study.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…As a result, the ability to model and predict fitness of team sport athletes as suggested above, may require performance tests that can be completed at high weekly frequencies. The vertical jump is the most popular means of obtaining frequent assessments of an athlete's physical capability and can be used daily without causing acute or chronic declines in performance [20] Additionally, a range of mechanical variables (e.g. impulse, power, rate of force development) can be extracted during vertical jumps to assess various features of the neuromuscular system [17,21].…”
Section: Introductionmentioning
confidence: 99%